Impact of IsaA gene disruption: decreasing staphylococcal biofilm and alteration of transcriptomic and proteomic profiles - Ma, Pei Yee; Chong, Chun Wie; Thian, Leslie Lung Than; Sulong, Anita; Ho, Ket Li; Neela, Vasantha Kumari; Sekawi, Zamberi; Liew, Yun Khoon (Multidisciplinary Digital Publishing Institute, 2022)
Staphylococcus aureus expresses diverse proteins at different stages of growth. The immunodominant staphylococcal antigen A (IsaA) is one of the proteins that is constitutively produced by S. aureus during colonisation and infection. SACOL2584 (or isaA) is the gene that encodes this protein. It has been suggested that IsaA can hydrolyse cell walls, and there is still need to study isaA gene disruption to analyse its impact on staphylococcal phenotypes and on alteration to its transcription and protein profiles. In the present study, the growth curve in RPMI medium (which mimics human plasma), autolytic activity, cell wall morphology, fibronectin and fibrinogen adhesion and biofilm formation of S. aureus SH1000 (wildtype) was compared to that of S. aureus MS001 (isaA mutant). RNA sequencing and liquid chromatography–tandem mass spectrometry were carried out on samples of both S. aureus strains taken during the exponential growth phase, followed by bioinformatics analysis. Disruption of isaA had no obvious effect on the growth curve and autolysis ability or thickness of cell walls, but this study revealed significant strength of fibronectin adherence in S. aureus MS001. In particular, the isaA mutant formed less biofilm than S. aureus SH1000. In addition, proteomics and transcriptomics showed that the adhesin/biofilm-related genes and hemolysin genes, such as sasF, sarX and hlgC, were consistently downregulated with isaA gene disruption. The majority of the upregulated genes or proteins in S. aureus MS001 were pur genes. Taken together, this study provides insight into how isaA disruption changes the expression of other genes and has implications regarding biofilm formation and biological processes.